Domestic, Not Private: Feminine Proposals for Carabanchel PAU Expansion, Madrid, Spain - Ángel Cordero Ampuero; Paula Ruiz Usero; Marta Muñoz Martín (Feminismo/s)
This paper offers a gender-based analysis of collective space in the domestic realm, beyond privacy, produced in significant social housing case studies in the urban expansion of Carabanchel neighbourhood (Carabanchel PAU, Madrid, Spain). Designed at the beginning of the 21st century, this period involves the incorporation of women into young architectural teams. Thus, this study seeks to delve into the significance of this role through the detailed study of eleven cases. Focussing on the common spaces of housing buildings, these small elements seem to recall the passage from the safe to the unsafe environment, from the space of the reproductive labour to that of the intersectionality. Following this finding, we propose an incipient study of the transitional spaces between the private and the public, where contacts between neighbours and the exchange of care beyond the private sphere are celebrated, as well as the public representation of domestic life. The methodological approach has stablished four meaning aspects to analyse, related to inhabitants’ life and intended as architectural parameters: spaces for neighbourhood flows, both for residents and visitors; areas of activity and leisure, available for resident daily life; connections between these areas of activity and leisure and, finally, connections of the common areas with the dwellings. The aim is to investigate the extent to which the participation of women architects makes these spaces more effective for care giving—or simply, more suitable for the expansion of intimate life and socialisation with neighbours. The results provide optimistic data for the discipline and its capacity, through this type of sensitivity, to correct some of the errors in the system of production of public space.